Development of PADI2u mobile application for paddy management - Roslin, Nor Athirah (2021)
Precision agriculture is a farming management, including site-specific crop management to increase production by reducing the input cost and saving the environment. A previous study developed web-based paddy management, Web Paddy Geographic Information System (Web-GIS) (Web Precision Farmer©). This study overcomes the limitation of the previous study, such as accessibility and affordability, user to use the system from the computer. Most of the information of the paddy management available in paper-based system. The current mobile application focused on one component in paddy management only. This research aims to design and develop mobile application for paddy management (PADI2U), populate the database into a mobile application, and test User Acceptance Test (UAT) of the mobile application. PADI2U mobile application is an Android-based mobile application developed using online software Master App Builder (MAB). The advantage of PADI2U is that it contains NDVI analysis from aerial imagery captured by UAV to monitor the paddy health status. UAT was conducted to get feedback and acceptance level from users of PADI2U mobile application performance. From UAT result show a high percentage of acceptance of the PADI2U mobile application. The contribution of this research to the farming community is the development of mobile application technology to manage their paddy field.